Barriers and facilitators to the HPV vaccine: a multicenter qualitative study of French general practitioners - Arthur Tron; Vincent Schlegel; Juliette Pinot; Sébastien BRUEL; Marie Ecollan; Josselin Le Bel; Louise Rossignol; Aurélie Gauchet; Amandine Gagneux-Brunon; Judith Mueller; Anne-Sophie Banaszuk; Nathalie Thilly; et al. (BMC, 2024)
Abstract Background In France, human papillomavirus (HPV) vaccination coverage is low, with 30.7% of 17-year-old girls having received a complete HPV vaccination schedule in 2020. Aim To determine the perspective and behaviors of general practitioners (GPs) regarding HPV vaccination with their patients and if a reluctance is observed. Design and setting A qualitative study based on semi-directed individual interviews was conducted between December 2019 and December 2020. A representative sample of GPs with various profiles were included in 4 French regions. Method A purposive sampling was used and interviews were continued until data saturation was reached. The analysis was based on the grounded theory. Results Twenty-six GPs aged 29-66 years were interviewed. The measures taken by the French health authorities (lowering the target age, reimbursing the vaccine, extending the target population to boys) were perceived as facilitators. The reported barriers were organizational, due to low attendance of adolescents, and relational, mainly due to parental vaccine hesitancy. Physicians had to deal with fears about the perceived risks and concerns about sexuality conveyed by HPV vaccination and linked to the socio-cultural characteristics of the families. Physicians developed strategies, including scientific knowledge mobilization, empowerment of families by promoting health through prevention, repetition of the vaccination proposals, personal experience and relationship. Different practices were identified according to three GP typologies: effective, convinced but unpersuasive, and reluctant physicians. Conclusion Based on these results, specific interventions, including communication techniques, especially for hesitant or unpersuasive physicians, are needed to enable GPs to become more effective.